Four simple recommendations to encourage best practices in research software - Jiménez, Rafael C; Kuzak, Mateusz; Alhamdoosh, Monther; Barker, Michelle; Batut, Bérénice; Borg, Mikael; Capella-Gutierrez, Salvador; Chue Hong, Neil; Cook, Martin; Corpas, Manuel; Flannery, Madison; Garcia, Leyla; et al. (F1000Research, 2017)
Scientific research relies on computer software, yet software is not always developed following practices that ensure its quality and sustainability. This manuscript does not aim to propose new software development best practices, but rather to provide simple recommendations that encourage the adoption of existing best practices. Software development best practices promote better quality software, and better quality software improves the reproducibility and reusability of research. These recommendations are designed around Open Source values, and provide practical suggestions that contribute to making research software and its source code more discoverable, reusable and transparent. This manuscript is aimed at developers, but also at organisations, projects, journals and funders that can increase the quality and sustainability of research software by encouraging the adoption of these recommendations.
Keywords: guidelines; code; Open Science; recommendations; sustainability; quality; Open Source; software; FAIR; best practices